Extraction and purification of RNA from human carious dentine: an approach to enable bacterial gene expression studies - Bezerra, Daniela da Silva; Neves, Beatriz Gonçalves; Guedes, Sarah Florindo de Figueiredo; Regis, Wanessa Fernandes Matias; Stipp, Rafael Nobrega; Rodrigues, Lidiany Karla Azevedo (Journal of Health & Biological Sciences, 2019)
Background: RNA isolation from bacteria within dentine caries lesions could be difficult due to reduced amount of collectable biomass and high mRNA instability. Attempting to overcome this challenge we describe one protocol developed to extract and purify total RNA from dentine lesions. Objective: customize a bacterial RNA extraction and purification method from human carious dentine. Methods: quantity and purity of extracted RNA were measured with a microvolume UV-VIS spectrophotometer, RNA integrity was assessed by standard denaturing agarose gel electrophoresis and images were captured under ultraviolet light with camera and analyzed. DNase treatment removed genomic DNA and an additional step of purification was carried out in silica spin column. Results: final yield (ng/μl) was 67.01 ± 22.33, absorbance ratio A260/A280 = 2.0 ± 0.07 and RNA integrity were obtained. The purified samples were reversely transcribed and the expression of atpD and fabM gene from Streptococcus mutans analyzed by quantitative real-time PCR. Conclusion: the extraction methodology developed produced high-quality RNA from dentine microbiota for transcriptional analysis.